Paraoxonase-2 modulates stress response of endothelial cells to oxidized phospholipids and a bacterial quorum-sensing molecule - Kim, Juyong Brian (2011)
OBJECTIVE: Chronic infection has long been postulated as a stimulus for atherogenesis. Pseudomonas aeruginosa infection has been associated with increased atherosclerosis in rats, and the bacteria produce a quorum-sensing molecule 3-oxo-dodecynoyl-homoserine lactone (3OC12-HSL) that is critical for colonization and virulence. Paraoxonase 2 (PON2) hydrolyzes 3OC12-HSL and also protects against the effects of oxidized phospholipids thought to contribute to atherosclerosis. We now report the response of human aortic endothelial cells (HAEC) to 3OC12-HSL and oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphocholine (Ox-PAPC) in relation to PON2 expression. METHODS AND RESULTS: Using expression profiling and network modeling, we identified the unfolded protein response (UPR), cell cycle genes, and the MAPK signaling pathway to be heavily involved in the HAEC response to 3OC12-HSL. The network also showed striking similarities to a network created based on HAEC response to Ox-PAPC, a major component of minimally-modified LDL. HAEC in which PON2 was silenced by siRNA showed increased pro-inflammatory and UPR responses when treated with 3OC12-HSL or Ox-PAPC. CONCLUSION: 3OC12-HSL and Ox-PAPC influence similar inflammatory and UPR pathways. Quorum sensing molecules such as 3OC12-HSL contribute to the pro-atherogenic effects of chronic infection. The anti-atherogenic effects of PON2 include destruction of quorum sensing molecules.